The provenance of marble artefacts from the roman metropolis of carnuntum (austria) la procedencia de artefactos de mármol de la metrópoli romano “carnuntum”, austria (2010)
This study has investigated the provenance of 116 marble objects from the important Roman metropolis of Carnuntum. In order to obtain the maximum information on the entire collection of the marble objects they were therefore divided into nine groups according to their macroscopic properties, prior to selecting those objects to be sampled for laboratory investigation. The results of the macroscopic, microscopic and geochemical investigations showed that most of the coarse and medium grained marbles originated from Gummern in Carinthia (Austria) or from Pohorje (Slovenia). The fine grained marbles were, however, mostly imported from the Mediterranean.